(untitled) (Texas Journal of Philology, Culture and History, 2024)
In the classification of terms related to each field, they are divided into certain thematic groups. It can be seen that there are a number of thematic groups in the classification of Uzbek theater terms. This article analyzes the Uzbek language terms by dividing them into thematic and lexicalsemantic groups.